2007
DOI: 10.1177/154193120705101808
|View full text |Cite
|
Sign up to set email alerts
|

The effect of display size on performance of operational tasks with UAVs

Abstract: The user-Interface of military dismounted systems has extreme influence on soldiers' ability to complete their missions and to protect themselves during combat. This work focused on the type of displays required to retrieve information from an unmanned aerial vehicle (UAV) in operational situations. Twenty IDF soldiers with limited experience in operating UAVs, participated in this simulated study of display-size preferences. In the 3 × 2 within subject design, participants used 3 types of displays on two miss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Focusing on the interaction between display type and feed color showed that B/W feed generated longer response times in the HHMD, and shorter ones for the 7" and for the 12" Tablet. As discussed in previous studies (Minkov et al, 2007, Minkov & Oron-Gilad, 2009, Minkov et al, 2010 using the HHMD may be more problematic in complex tasks as navigation and orientation. Here, the effect of feed color may be another evidence for the need of more naturalistic vision (e.g.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Focusing on the interaction between display type and feed color showed that B/W feed generated longer response times in the HHMD, and shorter ones for the 7" and for the 12" Tablet. As discussed in previous studies (Minkov et al, 2007, Minkov & Oron-Gilad, 2009, Minkov et al, 2010 using the HHMD may be more problematic in complex tasks as navigation and orientation. Here, the effect of feed color may be another evidence for the need of more naturalistic vision (e.g.…”
Section: Discussionmentioning
confidence: 93%
“…Recent studies aimed to investigate and map the factors that affect the use of imagery from UVs. Factors as UV type Clark, 2008, Oron-Gilad et al, 2011), display type, and type of task (Minkov, Perry & Oron-Gilad, 2007;Minkov & Oron-Gilad, 2009, Minkov et al, 2010 were among those factors. Another factor that may affect the ability and quality of UV video feeds utilization is the color and quality of the feed.…”
Section: Introductionmentioning
confidence: 97%
“…The experiment was needed due to inconsistencies in the research literature. Several past studies found no performance differences created by reduced display size [1,11,13,18,21,22]. However, there were some conflicting results, with some investigations indicating a benefit of larger displays, albeit in different task demand situations not directly generalizable to the dismounted robot control situation.…”
Section: Display Sizementioning
confidence: 89%
“…Equipment designers must consider not only the range of devices that soldiers will use, but also their context of use. Previous studies (Minkov, Perry & Oron-Gilad, 2007;Minkov & Oron-Gilad, 2009;Oron-Gilad, Redden & Minkov (submitted)) have shown task dependent differences among display types with regard to soldiers' performances. Furthermore, Oron-Gilad et al (submitted) demonstrated task related differences when utilizing UAV versus Unmanned Ground Vehicle (UGV) feed.…”
Section: Introductionmentioning
confidence: 90%